PENGARUH BRAND AWARENESS TERHADAP BRAND EXTENSIBILITY DAN REPURCHASE INTENTION MELALUI QUALITY PERSEPTION - Murniyati Murniyati; Ajat Sudrajat (Yayasan Akrab Pekanbaru, 2019)
This study aims to examine the effect of Brand Awareness on Repurchase Intention and Brand Extensibility through the Quality Perception. The research was carried out in different places to get the respondent. By reason of these places facilitate researchers to find respondents. Population and sample this research is the user's Lifebuoy, which amounts to 150 respondents. Analytical techniques used to analyze the influence of variables on Brand Awareness and Brand Extensibility through the Quality Perception Repurchase Intention is to use the SEM (Structural Equation Model). The analysis shew that there was a significant positive effect on Brand awareness toward Brand extensibility and Repurchase Intention through Quality Perceptions. The conclusion of this study is that consumers have brand awareness Lifebuoy positive effect on Quality Perception. This suggests that the higher level of brand awareness in the minds of consumers will increase as well.